PERAN MUSEUM BRAWIJAYA SEBAGAI WAHANA INTERNALISASINILAI-NILAI KEBANGSAAN - Safitri, Auliah (Jurnal Civic Hukum, 2016)
To build Indonesia should be grounded on the values of the existing nationality. But at present, these values began to fade. The next generation is losing confidence in their nation. So need an effort to make national values can flourish and inspired by all the people to build the nation?s character. Brawijaya Museum is one of the institutions that can strengthen the character of nationalism youth through collections owned. This is a descriptive study using qualitative methods. Its collection techniques are observation, interviews, and documentation. The method are data analysis, data reduction, data presentation, and conclusions. The results showed that: a) Museum Brawijaya as a form of role in the values of nationality is to tell museum collections to visitors and participate or actively in exhibitions organized by relevant institutions, b) Management of the museum include ways attract the attention of visitors, human resources, funding, technical management of the collection and management of the library, c) Visitors response after visiting the museum is satisfied that a lot of national values that they can get that put the interests of the nation above personal interests, capable and willing to sacrifice for the nation and country, love homeland and nation, proud nation and state of Indonesia, uphold the unity of the nation and the state.